IDENTIFYING FAKE PROFILES ACROSS ONLINE SOCIAL NETWORKS BY USING NEURAL NETWORK (International Journal of Food and Nutritional Sciences, 2022)
Worldwide, social networking services are used by millions of people. The wayusers interact with social media platforms like Twitter and Facebook has a significant impact ondaily life, often with negative outcomes. Popular social networking sites have been used as atarget by spammers to spread a lot of harmful and irrelevant content. For instance, Twitter hasbecome one of the most widely used platforms ever, which has led to an overwhelming amountof spam. Fake users waste resources and hurt real users by sending unwanted tweets to users inorder to promote businesses or websites